2018
DOI: 10.1515/chem-2018-0053
|View full text |Cite
|
Sign up to set email alerts
|

Modelling world energy security data from multinomial distribution by generalized linear model under different cumulative link functions

Abstract: Abstract:In the concept of the aesthetic formation of knowledge and its as soon as possible and success-oriented application, insights and profits without the reference to the arguments developed around 1900. The main investigation also includes the period between the entry into force and the presentation in its current version. Their function as part of the literary portrayal and narrative technique. Keywords: Function, transmission, investigation, principal, period Dedicated to Paul Placeholder Studies and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Hope therapy is a healthcare program based on Snyder's hope therapy designed to enhance hopeful thinking and strengthening activities related to pursuit of goal, which is derived from cognitive-behavioral therapies, solution-based treatments and fictional and narrative treatment (Snyder and Peterson, 2000). In this treatment, participants first get acquainted with the principles of the theory of hope therapy and then they are taught how to apply these principles in their lives (Da Silva Soares et al, 2018;Danby et al, 2018;Eglitis and Popov, 2018;Iyit, 2018;Kmita et al, 2018;Moreno-Fernandez et al, 2018;Taki et al, 2018). Participants learn how to determine important, achievable, and measurable goals, set multiple paths to move toward these goals, identify the motivational resources and interactions of each obstacle to its motivation, review progress towards the goal, and adjust the targets and passages as needed (Ahamed et al, 2017;Khosravi et al, 2018;Martinez Macias et al, 2017;Singh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Hope therapy is a healthcare program based on Snyder's hope therapy designed to enhance hopeful thinking and strengthening activities related to pursuit of goal, which is derived from cognitive-behavioral therapies, solution-based treatments and fictional and narrative treatment (Snyder and Peterson, 2000). In this treatment, participants first get acquainted with the principles of the theory of hope therapy and then they are taught how to apply these principles in their lives (Da Silva Soares et al, 2018;Danby et al, 2018;Eglitis and Popov, 2018;Iyit, 2018;Kmita et al, 2018;Moreno-Fernandez et al, 2018;Taki et al, 2018). Participants learn how to determine important, achievable, and measurable goals, set multiple paths to move toward these goals, identify the motivational resources and interactions of each obstacle to its motivation, review progress towards the goal, and adjust the targets and passages as needed (Ahamed et al, 2017;Khosravi et al, 2018;Martinez Macias et al, 2017;Singh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The "linear predictor" part and the "link function" of the GLM can be given as follows (Myers et al [59], İyit [60]);…”
Section: Methodsmentioning
confidence: 99%
“…Generalized linear mixed model (GLMM) approach is an extension of the GLM approach by adding random effect(s) to the "linear predictor" part. A general form of the "link function" of the GLMM as a function of the conditional mean of the response variable given the random effect term () u  can be given as follows (McCulloch and Searle [61], Stroup [62], İyit et al [63]);…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the fatty acid derivatives metabolic pathway of apple aroma (Robert, et al, 2007), hexanal transformed by linoleic acid hydroperoxide could generate 2-methylbutanol which can produce 2-isoamyl acetate by the alcohol acyltransferase in presence of ADH (Dudareva et al, 2008). And also, in the mature process of fruits, the expression level of ADH has important influence on the diversity of aroma components, especially the content of aldehydes and alcohols (Iyit, 2018;Jiang et al, 2018;Khan et al, 2018). Studies have indicated that the increase of ethylene content would lead to lower expression of ADH (Defilippi et al, 2005), while the increase of alcohols would make genetically modified fruit more flavor (Speirs J et al, 1998).…”
Section: Introductionmentioning
confidence: 99%